Promotion of Paragliding Sports Tourism Wayu Sigi Regency In Terms of Aspects of Community Welfare and Visitor Satisfaction - Moh. Rifki; Bambang Budi Raharjo; Sulaiman Sulaiman (JUARA : Jurnal Olahraga, 2023)
This study aims to analyze the promotion of Wayu paragliding sports attractions in terms of the welfare of the people who work at the attraction and visitor satisfaction. The design of this study uses methods (Mixed Methods) combining quantitative and qualitative research with the Convergent Parallel Design design. Research data collection techniques using observations in the field with media (observation, interviews, questionnaires, and documentation). Qualitative research data analysis techniques use the help of NVivo 12 software to find out the results of interviews with four respondents. Meanwhile, quantitative research data from filling out questionnaires from 15 workers at tourist attractions and 387 tourist visitors, then analyzed descriptive percentages with the help of Microsoft Excel and SPSS 22 software. The results of qualitative research data show that (a) the lack of use of social media, (b) not promoting in detail tourist attractions, (c) the strategic location of tourist attractions that show the scenery of Palu City, Wayu paragliding sports attractions as training grounds, championship events, camping grounds, and places for national day commemoration ceremonies (c) create jobs for the community, access to poor locations, the facilities, and infrastructure in the Wayu paragliding sports attraction is quite good. Meanwhile, the results of quantitative research data on community welfare and visitor satisfaction are in the moderate category. Based on the results of the study, it can be concluded that the Wayu paragliding sports attraction has potential that can be promoted through social media judging from the supporting facilities and infrastructure than its strategic location as a paragliding sports venue and camping ground as well as support from other uniqueness in the Wayu paragliding sports attraction. It can significantly contribute to the improvement of community welfare and the satisfaction and comfort of visitors.